2003
DOI: 10.1002/jcla.10069
|View full text |Cite
|
Sign up to set email alerts
|

Serum microminerals and the indices of lipid metabolism in an apparently healthy population

Abstract: Serum copper and zinc concentrations were measured in 560 apparently healthy Kuwaitis (238 males and 322 females) aged 15-80 years to assess micromineral effect on the indices of lipid metabolism. Following the recommended guidelines of the European Atherosclerosis Society (EAS) and the National Cholesterol Education Program Expert Panel (NCEPEP), the incidence of dyslipidemia was assessed from enzymatic assay data of triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
6
12
1
Order By: Relevance
“…In agreement with the present study, an earlier Lebanon study showed that serum copper was positively associated with TC and LDL cholesterol [18]. A similar result was also found in Kuwaitis, and the study indicated that high serum copper concentration was not only associated with high TC and LDL cholesterol, but also with high TG [16]. Furthermore, the Slovakia study showed that high serum copper status was associated with increased levels of TC and LDL cholesterol but with decreased levels of HDL cholesterol among men [19].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with the present study, an earlier Lebanon study showed that serum copper was positively associated with TC and LDL cholesterol [18]. A similar result was also found in Kuwaitis, and the study indicated that high serum copper concentration was not only associated with high TC and LDL cholesterol, but also with high TG [16]. Furthermore, the Slovakia study showed that high serum copper status was associated with increased levels of TC and LDL cholesterol but with decreased levels of HDL cholesterol among men [19].…”
Section: Discussionsupporting
confidence: 82%
“…Most studies suggested that serum copper level was positively associated with TC [16][17][18], LDL cholesterol [16,19], or TG [16,20,21]. However, some studies found no evidence of associations between serum copper and TC [20], TG [17,18,22], LDL cholesterol [17,23], and HDL cholesterol [16,21,22]. In addition, other studies found that serum copper was inversely related to TC [23] and HDL cholesterol [23][24][25].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…ThuillerJeteau et al (1987) reported increased Cu status in hypercholesterolemia. Abiaka et al (2003) observed that unlike in animal studies, copper excess in humans is associated with hypercholesterolemia and therefore will predispose to atherosclerosis. Aoyama et al (1999) observed that serum cholesterol did not increase in rats fed with copper-deficient diets, though copper in serum decreased markedly in rats.…”
Section: Discussionmentioning
confidence: 78%
“…A high level of MT prevents Cu absorption/uptake into the intestine, liver, and kidney (Disilvestro & Cousins, 1983). Cu deficiency adversely affects lipid metabolism by decreasing HDL-cholesterol (Abiaka et al, 2003) and predisposes to cardiovascular abnormalities, by a mechanism which may involve free radical scavenging (Klevay et al, 1994). Moreover, Cu deficiency impairs lysyl oxidase function, an indispensable enzyme for structural integrity of vascular connective tissues (Allen & Klevay, 1978).…”
Section: Zinc and Biological Functionsmentioning
confidence: 99%